Introduction to the Special Issue “Scientific Breakthroughs to Fruit and Vegetable By-Product Valorization in the Food Sector” - Amalia Conte; Matteo A. Del Nobile (Foods, 2023)
We are pleased to present this Special Issue, which includes five papers that highlight important research activities in the field of fruit and vegetable by-product valorization [...]